The clash between state law and customary law in the settlement of inheritance disputes - Saofi, M. Sulhan (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Inheritance disputes in indigenous communities frequently arise from tensions between state law and living customary law. In Toraja society, inheritance distribution is traditionally governed by patrilineal norms, whereas state law emphasizes equal inheritance rights for sons and daughters, creating practical and normative friction in dispute resolution. Prior socio-legal discussions on legal pluralism indicate that customary authority often remains dominant in community life, yet state legal standards increasingly frame rights-based protection, including gender equality, as a core benchmark in adjudication. This study aims to examine how state legal norms and Toraja customary rules interact, compete, and shape outcomes in inheritance dispute resolution, and to identify a feasible pathway for harmonization that can support fairness and social justice. Methods: This research employs a juridical-normative method using a statute approach and a conceptual approach. Legal materials were collected through library research, including relevant legislation, judicial reasoning patterns in inheritance disputes, and doctrinal writings on customary law, gender equality, and legal pluralism, and then analyzed qualitatively through systematic interpretation and legal argumentation. Findings: The analysis shows that Toraja customary law remains highly authoritative and socially binding, influencing dispute settlement preferences and community compliance, but it tends to produce unequal outcomes where inheritance is allocated primarily through male lineage. Conversely, state law provides stronger normative support for gender-equal inheritance rights, offering broader protection for daughters when disputes reach formal legal institutions. The findings indicate that the tension is not merely procedural but conceptual: customary legitimacy is grounded in communal continuity, while state law prioritizes equality-based rights, requiring adjudication that can translate both values into a reasoned, socially acceptable decision. Conclusion: Harmonization is necessary to ensure inheritance dispute resolution is both socially legitimate and substantively just, particularly in safeguarding gender equality without disregarding customary authority. Novelty/Originality of this article: This article contributes an integrated normative model for resolving Toraja inheritance disputes by positioning judicial dialogue between state law and customary law as a structured mechanism for balancing communal legitimacy and equality-based rights within a plural legal setting.